A comparison of orbitally‐shaken and stirred‐tank bioreactors: pH modulation and bioreactor type affect CHO cell growth and protein glycosylation. (11th August 2016) - Monteil, Dominique T.; Juvet, Valentin; Paz, Jonathan; Moniatte, Marc; Baldi, Lucia; Hacker, David L.; Wurm, Florian M.
Abstract : Orbitally shaken bioreactors (OSRs) support the suspension cultivation of animal cells at volumetric scales up to 200 L and are a potential alternative to stirred‐tank bioreactors (STRs) due to their rapid and homogeneous mixing and high oxygen transfer rate. In this study, a Chinese hamster ovary cell line producing a recombinant antibody was cultivated in a 5 L OSR and a 3 L STR, both operated with or without pH control. Effects of bioreactor type and pH control on cell growth and metabolism and on recombinant protein production and glycosylation were determined. In pH‐controlled bioreactors, the glucose consumption and lactate production rates were higher relative to cultures grown in bioreactors without pH control. The cell density and viability were higher in the OSRs than in the STRs, either with or without pH control. Volumetric recombinant antibody yields were not affected by the process conditions, and a glycan analysis of the antibody by mass spectrometry did not reveal major process‐dependent differences in the galactosylation index. The results demonstrated that OSRs are suitable for recombinant protein production from suspension‐adapted animal cells. © 2016 American Institute of Chemical Engineers Biotechnol. Prog ., 32:1174–1180, 2016